MANAJEMEN KEPEMIMPINAN DI LEMBAGA PENDIDIKAN ISLAM - Jayadi, Usman; Muttaqin, Zainul; Hapipi, Hapipi (Lafadz Jaya Publisher, 2022)
This study aims to find out about leadership management and its influence, in order to create in Islamic educational institutions. Leadership has a very strategic and important role in creating good quality education. Therefore, education and training are needed for leaders to strengthen their leadership management in each agency. This study uses a survey type quantitative approach. The data collection technique is done through observation, interviews, documentation, and questionnaires. The questionnaire was tested to test the validity, reliability and objectivity of the instrument, using the total item correlation technique which is the basis of the Pearson correlation. From the survey results, seven interval classes were obtained with the highest significant gain in class 4 (32.50%) and the lowest in class 7 (2.50%). The survey instrument includes 4 aspects of implementation, 1) guidance, 2) supervision, 3) assessment, and 4) monitoring. The results of the study indicate that it is very important to carry out education and training in order to improve the quality of leadership management in Islamic educational institutions.